The Fibonacci Numbers
We define the n -th fibonacci number as follows
  • F 0 = 0 and F 1 = 1
  • F n = F n 1 + F n 2 for every n 2
Sum Equals Jump 2 minus One
For every n N 0 we have F 0 + F 1 + + F n = F n + 2 1
We prove it by induction, for the base case F ( 0 + 2 ) 1 = ( F 1 + F 0 ) 1 = 1 + 0 1 = 0 = F 0 as needed. Next assume it holds true for k N 0 and then we want to prove that F k + 3 1 = F 0 + + F k + 1 , we can handle the sum with the inductive hypothesis, so that F 0 + + F k + F k + 1 = ( F k + 2 1 ) + F k + 1 = F k + 3 1 as needed.